Monitoring Korosi Discharge Conveyor G pada Tambang Batubara PT GHI di Kabupaten Banjar Provinsi Kalimantan Selatan - Azi Faturahman Fachreza; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyor is a conveyance used to move coal from one place to another continuously. The conveyor is supported by a static building structure made of carbon steel. Carbon steel is used because it is strong and resistant to temperature and pressure, but is susceptible to corrosion due to the influence of its environment. This research was conducted to determine the type of corrosion, corrosion control methods, Corrosion Rate, and Remaining Service Life of the conveyor structure.This research uses the thickness reduction measurement method. Measurements are made to determine the actual thickness of the conveyor structure which has a design life of 15 years and a service life of 7 years. The conveyor structure is above ground level, and has a length of 94 meters which is divided into 3 segments and 25 test points. Measurements were taken using a smart sensor ultrasonic thickness gauge TT 130.The type of corrosion that occurs on the conveyor structure is uniform corrosion. The corrosion control method used is a coating method with a three-layer system using Seaguard 5000 as a primary coating, Sherglass FF as an intermediate coating, and Aliphatic acrylic modified polyurethane as a top coating. Corrosion Rates that occur at each test point range from 0.1543 - 0.2843 mm / year which falls into the "Good" category based on the relative corrosion resistance of steel. Remaining Service Life of the conveyor structure ranges from 9.73 - 12.43 years which shows that all test points are predicted to reach their design life. Abstrak. Conveyor merupakan suatu alat angkut yang digunakan untuk memindahkan material dari suatu tempat ke tempat lainnya secara continue. Conveyor tersebut didukung oleh adanya suatu struktur bangunan statis yang terbuat dari baja karbon. Baja karbon digunakan karena sifatnya yang kuat dan tahan terhadap temperatur dan tekanan, namun rentan untuk mengalami korosi akibat dari pengaruh lingkungannya. Penelitian ini dilakukan untuk mengetahui jenis korosi, metode pengendalian korosi, Corrosion Rate dan Remaining Service Life struktur conveyor. Penelitian ini menggunakan metode pengukuran pengurangan ketebalan. Pengukuran dilakukan untuk mengetahui tebal aktual struktur conveyor yang memiliki umur desain 15 tahun dan umur pakai 7 tahun. Struktur conveyor berada di atas permukaan tanah dan memiliki panjang 94 meter yang dibagi ke dalam 3 segmen dan 25 test point. Pengukuran tebal aktual dilakukan menggunakan alat Smart Sensor Ultrasonic Thickness Gauge TT 130. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang digunakan adalah metode coating dengan sistem Three layers, yaitu Seaguard 5000 sebagai primer coating, Sherglass FF sebagai intermediate coating dan Aliphatic acrylic modified polyurethane sebagai top coating. Corrosion Rate yang terjadi pada tiap test point berkisar antara 0,1543 – 0,2843 mm/tahun yang termasuk ke dalam kategori “good” berdasarkan ketahanan korosi relatif baja. Remaining Service Life struktur conveyor berkisar antara 9,73 – 12,43 tahun yang menunjukkan seluruh test point diprediksi dapat mencapai umur desainnya.